Brand Islam : the marketing and commodification of piety - Shirazi, Faegheh, 1952- (University of Texas Press, 2016)
From food products to fashions and cosmetics to children's toys, a wide range of commodities today are being marketed as "halal" (permitted, lawful) or "Islamic" to Muslim consumers both in the West and in Muslim-majority nations. However, many of these products are not authentically Islamic or halal, and their producers have not necessarily created them to honor religious practice or sentiment. Instead, most "halal" commodities are profit-driven, and they exploit the rise of a new Islamic economic paradigm, "Brand Islam," as a clever marketing tool. Brand Islam investigates the rise of this highly lucrative marketing strategy and the resulting growth in consumer loyalty to goods and services identified as Islamic. Faegheh Shirazi explores the reasons why consumers buy Islam-branded products, including conspicuous piety or a longing to identify with a larger Muslim community, especially for those Muslims who live in Western countries, and how this phenomenon is affecting the religious, cultural, and economic lives of Muslim consumers. She demonstrates that Brand Islam has actually enabled a new type of global networking, joining product and service sectors together in a huge conglomerate that some are referring to as the Interland. A timely and original contribution to Muslim cultural studies, Brand Islam reveals how and why the growth of consumerism, global communications, and the Westernization of many Islamic countries are all driving the commercialization of Islam.